Non-corrosive green lubricants: strengthened lignin–[choline][amino acid] ionic liquids interaction via reciprocal hydrogen bonding. Issue 81 (3rd September 2015) - Mu, Liwen; Shi, Yijun; Guo, Xiaojing; Ji, Tuo; Chen, Long; Yuan, Ruixia; Brisbin, Logan; Wang, Huaiyuan; Zhu, Jiahua
<x xml:space="preserve">Abstract</x> Lignin and [choline][amino acid] ionic liquids with reciprocal hydrogen bonding in between have been demonstrated to be excellent non-corrosive green lubricants in boundary lubrication applications.